2017
DOI: 10.1111/jace.15002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and electric field on upconversion luminescence in Er3+‐Yb3+ codoped Ba0.8Sr0.2TiO3 ferroelectric ceramics

Abstract: Optical and electrical properties of 1%Er 3+ and different Yb 3+ content (1ExY) codoped Ba 0.8 Sr 0.2 TiO 3 (BST) ferroelectric ceramics fabricated by the solid-phase reaction were investigated. Under 980 nm pump condition, two green emission bands at 525 and 549 nm wavelength corresponding to, 2 H 11/2 ? 4 I 15/2 and 2 S 3/2 ? 4 I 15/2 transitions, and two red emission bands at 655 and 668 nm wavelength attributed to 4 F 9/2 ? 4 I 15/2 transition are observed. The temperature-sensing behaviors, calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Ferroelectric materials with luminescent properties are an important class of optoelectronic functional materials that possess great potential for applications in spintronics, photovoltaics, optical-electrical-mechanical actuators, and so on 1 . To date, research on luminescent ferroelectrics has mainly focused on inorganic perovskites with a general formula of ABO 3 (where A and B are metal ions with different sizes), which have been widely investigated and found to have numerous applications over the last few decades 2,3 . However, due to the pressing environmental and energy issues, their time-consuming, high-cost, and energy-intensive fabrication processes severely hinders the future developments of these inorganic ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric materials with luminescent properties are an important class of optoelectronic functional materials that possess great potential for applications in spintronics, photovoltaics, optical-electrical-mechanical actuators, and so on 1 . To date, research on luminescent ferroelectrics has mainly focused on inorganic perovskites with a general formula of ABO 3 (where A and B are metal ions with different sizes), which have been widely investigated and found to have numerous applications over the last few decades 2,3 . However, due to the pressing environmental and energy issues, their time-consuming, high-cost, and energy-intensive fabrication processes severely hinders the future developments of these inorganic ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Barium titanate (BaTiO 3 ) is probably the most widely studied and used multifunctional ferroelectric ceramic. A great deal of experimental and theoretical researches on both aliovalent and isovalent doping in BaTiO 3 has produced great insights, which are constantly growing. ,,,,, …”
Section: Ferroelectricsmentioning
confidence: 99%
“…As a result of the excellent UCL properties, perovskite-type oxides are also used as temperature sensor materials. Such temperature sensing is a noncontact measurement with high sensitivity, high signal discriminability, and broad range dynamic imaging [16,24,26,27] . In this respect, several literatures have investigated the effects of temperature on the UCL in the RE-doped perovskite-type oxides.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, several literatures have investigated the effects of temperature on the UCL in the RE-doped perovskite-type oxides. Sun et al reported a maximum sensitivity of 1.07 × 10 −2 K −1 at room temperature for the Er 3 , Yb 3 co-doped Ba 0.8 Sr 0.2 TiO 3 ferroelectric ceramics [27] . Meanwhile, Mahata et al demonstrated that Zn 2 ions can improve the temperature-sensing performance of the perovskite BaTiO 3 ∶Er 3 =Yb 3 nanophosphors [16] .…”
Section: Introductionmentioning
confidence: 99%